Comments on intermetallic thermochemistry - Borzone G.; Raggio R.; Ferro R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The need of a concerted multi-disciplinary approach in the investigation of intermetallic systems and the role of thermochemistry are underlined. The activity carried out in the Author’s laboratory in the alloy thermodynamics is summarized. The different instruments (calorimeters) built in laboratory are briefly presented and their performance discussed. The results obtained in the measurement of the enthalpy of formation mainly of several rare earth alloys are described. The characteristics of the Eu and Yb thermochemistry and crystallochemistry are finally underlined.